A hybrid method based on genetic algorithm approach to the estimation of scattering centers for radar imaging - Gultekin, O.; Erer, I.; Gunel, T. (IEEE, 2004)
In this work, a novel scattering center extraction method using genetic algorithm based CLEAN is proposed. Initial values for optimization parameters are estimated from the power spectra of the measured data using the Fourier transform. The proposed method reduces computational time compared to existing evolutionary programming (EP) based approaches.